Artificial Intelligence in the Perspective of Islamic Psychology - Puput Mulyono; Kresna Agung Yudhianto (Journal of Islamic Psychology and Behavioral Sciences, 2026)
The development of computer technology and artificial intelligence (AI) has enabled machines to emulate human abilities in logical thinking, calculation, and interaction. However, from the perspective of Islamic psychology, such capabilities cannot replace the spiritual dimensions of humans qalb (heart) and nafs (soul) which are the centers of moral and spiritual consciousness. This study is a library research that analyzes AI from Islamic and ethical perspectives, aiming to describe systematically and comprehensively the relationship between technological advancement and Islamic values. Islam emphasizes that technology serves as a tool for human benefit, not a substitute for human nature; therefore, its development must be grounded in ethical principles aligned with sharia, including justice (‘adl), trust (amanah), compassion (rahmah), and respect for human dignity. By integrating the concepts of tazkiyatun nafs (purification of the soul), tawakkal (trust in God), and ikhtiar (effort), this study highlights the importance of maintaining balance between intellect and spirituality in the use of AI so that technology functions as a means of worship, enlightenment, and mercy for all creation (rahmatan lil ‘alamin).